Pandemic fatigue and attenuated impact of avoidance behaviours against COVID-19 transmission in Hong Kong by cross-sectional telephone surveys - Gabriel M Leung; Peng Wu; Huizhi Gao; Zhanwei Du; Tim K Tsang; Jingyi Xiao; Songwei Shan; Qiuyan Liao (BMJ Open)
Objectives This study aims to explore the attenuated impact of reported avoidance behaviours adherence on the transmission of COVID-19 through cross-sectional surveys in Hong Kong, in order to make up for the lack of research on avoidance behaviours fatigue.Design 40 cross-sectional telephone surveys.Setting All districts in Hong Kong.Participants 31 332 Cantonese or English-speaking participants at age of 18 years or above.Methods We collected data on behaviours and estimated the average effective reproduction number (Rt) among the Hong Kong adult population during the COVID-19 epidemic wave in November–December 2020 and compared with the preceding epidemic in June–July 2020.Results We observed a reduction in adherence to voluntary avoidance behaviours due to pandemic fatigue, but continued adherence to regulated avoidance behaviours. The average Rt during the post-work from home period was higher in November–December wave with estimated Rt of 0.81 (95% CI: 0.75 to 0.87) compared with the June–July wave with an Rt of 0.67 (95% CI: 0.60 to 0.75).Conclusions The declined effectiveness of social distancing interventions in reducing COVID-19 transmission was associated with fatigue with voluntary avoidance behaviours in Hong Kong population, implying a need for the government to reinvigorate the public to maintain effective pandemic control.